Toxicity in the vestibular system: A literature review - Aron Ferreira da Silveira; Maiara Santos Goncalves (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2019)
The objective of this study was to systematically review the bibliographies dealing with vestibular toxicity, its morphological and functional damages. This review was carried out with a search in the electronic databases Virtual Health Library (VHL), Medical Literature Analysis and Retrieval System Online (MedLine) with the tool PubMed, Latin American and Caribbean Literature in Health Sciences (LILACS) and Scientifi c Electronic Library Online (SciELO), from October to November / 2018. As a search strategy, the following keywords were used in Portuguese and their correspondents in English and Spanish: vestibular toxicity, vestibular ototoxicity and vestibulotoxicity. A total of 265 complete articles were collected in the databases searched. Of these, after the analysis, thirteen articles and a master's thesis were used. Articles range from 1977 to 2017, mostly involving American researchers. The toxicity of aminoglycoside antibiotics was the predominant issue, but other substances were also reported in less number. Most of the studies used as sample the experimental model. Predominant were studies whose substance searched had confi rmed vestibulotoxicity.